Next-generation sequencing of homologous recombination genes could predict efficacy of platinum-based chemotherapy in non-small cell lung cancer - Zhang, Linlin; Guan, Shasha; Meng, Fanlu; Teng, Lin; Zhong, Diansheng (Frontiers in Oncology, 2022)
Background: With the widespread use of next-generation sequencing (NGS) in clinical practice, an increasing number of biomarkers that predict a response to anti-tumor therapy in non-small cell lung cancer (NSCLC) has been identified. However, validated biomarkers that can be used to detect a response to platinum-based chemotherapy remain unavailable. Several studies have suggested that homologous recombination deficiency (HRD) may occur in response to platinum-based chemotherapy in ovarian cancer and breast cancer. However, currently there is a lack of proven and reliable HRD markers that can be used to screen for patients who may benefit from platinum-based chemotherapy, especially in NSCLC. Methods: NGS was used to screen for gene mutations, including homologous recombination (HR) genes and common driver gene mutations in NSCLC. Cox regression analysis was performed to identify potential clinicopathological or gene mutation factors associated with survival in patients receiving platinum-based chemotherapy, while Kaplan–Meier analysis with the log-rank test was performed to assess the effect of HR gene mutations on progression-free survival (PFS). Results: In a retrospective cohort of 129 patients with advanced NSCLC, 54 who received platinum-based chemotherapy with or without anti-angiogenic therapy were included in the analysis. Univariate and multivariate Cox proportional hazard regression analyses showed that HR gene mutations were associated with platinum-based chemotherapy sensitivity. Efficacy results indicated that the objective response rates (ORR) for patients with BRCA1/2 mutations and BRCA1/2 wild type were 75% and 30.4% (p=0.041), while the median PFS was 7.5 and 5.5 months (hazard ratio [HR], 0.52; 95% CI, 0.27–1.00; p=0.084), respectively. The ORRs of patients with HR gene mutations and HR gene wild type were 60% and 23.6% (p=0.01), and the median PFS was 7.5 and 5.2 months (HR, 0.56; 95% CI, 0.32–0.97; p=0.033), respectively. Conclusions: HR gene mutations show potential as promising biomarkers that may predict sensitivity to platinum-based chemotherapy in advanced and metastatic NSCLC.